Community reporting system: road violation - Roslan, M. Ridzuan; Ahmad Zabidi, Suriza (2019)
In the era of internet and wireless, an online community reporting system that is easy to use, and hustle free is much needed to allow the user to place a misconduct report to the relevant authority. The available system is inefficient and time-consuming since most are using web-based, which makes the user unwilling to make a report to the authority. The objective of this project is to design a system using an android application that is cost-effective and easy to use. The scope of this project is on the road violation reporting system. The outcome of the system will provide a user with an easy reporting system, and also the authority can manage the report easily. The development of the system is expected to enhance the reporting